Synergic Actions of BEA-Type Zeolites and Ultrasonic Irradiation in Conversion of Geraniol - Ramishvili, Ts.; Tsitsishvili, V.; Ivanova, I.; Kokiashvili, N.; Bukia, T.; Kurtsikidze, G. (Asian Journal of Chemistry, 2018)
The geraniol conversion reaction was initiated by the simultaneous action of micro- and micro-mesoporous BEA-type zeolites and ultrasonic irradiation (UMR-300B hybrid reactor, 25 kHz, 100-900 W; SRF-1, 20-60 kHz, 100 W). Geraniol by ultrasonic irradiation at 27-100 ºC, had a low degree of conversion, upto 2 %. Geraniol was a resistant to ultrasound in argon atmosphere solutions of N,N-dimethylformamide and methanol. In methanolic solution, geraniol was actively converted to linalool and to methyl ethers of linalool and nerol with the selectivity of 80 % on zeolite BEA-25 under ultrasonic irradiation in air at 30 ºC. Using BEA-type zeolite/ultrasonic-assisted reaction was increased the degree of conversion of geraniol, the selectivity and yield to linalool and nerol on the most active RBEA-25 zeolite by prolonged ultrasonic irradiation (1.5-5 h) or under combined ultrasound and microwave irradiation (US 300 W/MW 550 W, 1.5 h, 80 ºC).